THE EFFECT OF OPERATING CONDITION FOR CUMENE CRACKING ON THE PERFORMANCE OF PREPARED HX - ZEOLITE CATALYST - Abdul Halim A-K Mohammed (Journal of Engineering, 2009)
The present study reports the effect of temperature and liquid hourly space velocity (LHSV) on the cumene cracking reaction rate and selectivity by using a laboratory continuous flow unit with fixed bed reactor operating at atmospheric pressure. The prepared HX zeolite was made from Iraqi kaolin with good crystallinity .The activity and selectivity of prepared HX-zeolite was compared with standard HY zeolite and HX zeolite catalysts in the temperature range of 673-823K and LHSV of 0.7-2.5 h-1. It was found that the cumene conversion increases with increasing temperature and decreasing LHSV at 823K and LHSV of 0.7 h-1 the conversions 65.32, 42.88 and 59.42 mol% for HY, HX and prepared HX catalysts respectively and at LHSV of 2.5 h-1 and the same temperature the conversions decrease to 29.24, 12.53 and 22.89 mol%, respectively .It also found that the benzene yield increases with increasing temperature at 823K and LHSV of 0.7 h-1 the benzene yields were 58.79, 38.56 and 54.56 mol% for HY zeolite , HX zeolite and prepared HX zeolite, respectively and the selectivity to benzene is nearly constant over the studied temperatures range. The kinetics of cumene cracking ( the kinetics parameters-rate constant )and activation energy are used in this study to characterize differences between various catalysts. The reaction was found to be first order with activation energy equal to 78.58 , 89.10 and 97.77 kJ/mol for HY, prepared HX and HX , respectively.